1987
DOI: 10.1002/mrc.1260251004
|View full text |Cite
|
Sign up to set email alerts
|

Conformations of bryonolic acid and its derivatives in CDCl3 solution by 1H and 13C NMR spectroscopy

Abstract: Comparison of the 'H and I3C chemical shift data of bryonolic acid (D: C-friedoolean-8-en-3~-01-2Y-oic acid) and its derivatives (13 species) revealed that the conformational features of these compounds in CDCI, solution depend on whether the functional groups at C-29 are trigonal, such as COOCH3, or tetrahedral, such as CH,OH. In order to study the conformational features of these two groups of compounds, vicinal coupling constants between the protons on the E rings of the methyl ester of D : C-friedoolean-8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
4
19
0
Order By: Relevance
“…Using two-dimensional NMR techniques (COSY, HMQC and HMBC), it was possible to assign unequivocal the 1 H and 13 C NMR spectra. Some of the 13 C NMR assignments made by us differ slightly from those given by Greca et al, 13 but were in full agreement with the data reported by Kamisato et al 15 Although compound 2 was identified many years ago, only now a complete unambiguous assignment of the 1 H NMR spectrum has been achieved.…”
Section: Resultssupporting
confidence: 90%
“…Using two-dimensional NMR techniques (COSY, HMQC and HMBC), it was possible to assign unequivocal the 1 H and 13 C NMR spectra. Some of the 13 C NMR assignments made by us differ slightly from those given by Greca et al, 13 but were in full agreement with the data reported by Kamisato et al 15 Although compound 2 was identified many years ago, only now a complete unambiguous assignment of the 1 H NMR spectrum has been achieved.…”
Section: Resultssupporting
confidence: 90%
“…We synthesized 3, 4, 12 and 13 described in previous papers, 3,13) and also 16 derivatives, 2, 5-11 and 14-21. C-29 functional groups of these model compounds were designed to allow us to reveal the effect on the S : F population of C-29 functionality, i.e., whether the functional groups are trigonal or tetrahedral and the identity of the substituents linking to the C-29 carbon atoms.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Assignments of carbon chemical shifts of 2-21 were done by comparing the shift data with those of the related compounds 3,13) and recording distortion enhancement by polarization transfer (DEPT) and 1 H-detected heteronuclear multiple bond correlation (HMBC) spectra.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations